The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4049/immunohorizons.2100019
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Bone Morphogenetic Protein Receptor 1A in Germinal Centers and Long-Lived Humoral Immunity

Abstract: In response to T-dependent Ag, germinal centers (GC) generate bone marrow-resident plasma cells (BMPC) and memory B cells (MBC). In this study, we demonstrate that the bone morphogenetic protein receptor 1A (BMPR1A) signaling pathway, which regulates differentiation and self-renewal in multiple stem cell populations, regulates GC dynamics and resultant establishment of BMPC and MBC. Expression studies using quantitative PCR and novel Bmpr1a.IRES.EGFP reporter mice demonstrated that Bmpr1a expression is upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In addition to changes in X-linked gene expression, we identified autosomal transcriptional changes in Xist cKO B cells with SLE phenotypes. In CD11c+ ABCs from Xist cKO High mice, upregulated autosomal genes were enriched for genes involved in lymphocyte activation, including Bcl3 (important for antigen-specific autoantibody formation) 73 , Bmpr1a (upregulated in some memory B cell subsets) 74 , Cxcr4 (plays a role in B cell homeostasis and trafficking) 75 , and Fas (upregulated in ABCs from patients with SLE) 41 . In CD11c+ ABCs from pristane-treated Xist cKO mice, upregulated autosomal genes were enriched for genes involved in immune processes, including Pik3r6 (mediates signaling pathways that regulate proliferation, class-switch recombination, and plasma cell differentiation) 76 , Sh3kbp1 (poises B cells to respond to BCR stimulation) 77 , and Zbtb20 (involved in plasma cell differentiation via Irf4) 78 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in X-linked gene expression, we identified autosomal transcriptional changes in Xist cKO B cells with SLE phenotypes. In CD11c+ ABCs from Xist cKO High mice, upregulated autosomal genes were enriched for genes involved in lymphocyte activation, including Bcl3 (important for antigen-specific autoantibody formation) 73 , Bmpr1a (upregulated in some memory B cell subsets) 74 , Cxcr4 (plays a role in B cell homeostasis and trafficking) 75 , and Fas (upregulated in ABCs from patients with SLE) 41 . In CD11c+ ABCs from pristane-treated Xist cKO mice, upregulated autosomal genes were enriched for genes involved in immune processes, including Pik3r6 (mediates signaling pathways that regulate proliferation, class-switch recombination, and plasma cell differentiation) 76 , Sh3kbp1 (poises B cells to respond to BCR stimulation) 77 , and Zbtb20 (involved in plasma cell differentiation via Irf4) 78 .…”
Section: Discussionmentioning
confidence: 99%
“…The BMPR-IA signaling pathway regulates differentiation and self-renewal in several stem-cell populations in the germinal center. Mouse germinal-center B cells showed increased expression of BMPR-IA, and the targeted deletion of BMPR-IA impaired the germinal-center reaction and reduced differentiation from plasmablasts to antibody-producing plasma cells ( 161 ). One study identified that although human germinal-center B cells express high levels of BMPRI and low levels of BMPRII, naïve B cells show low levels of BMPRI and high levels of BMPRII ( 162 ).…”
Section: Interactions Of Bmps Activins and Gdfs With The Adaptive Imm...mentioning
confidence: 99%